Stabilization policy and business cycle phases in Europe: A Markov Switching VAR analysis - Michel Beine; Bertrand Candelon; Khalid Sekkat (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
Most of the empirical studies dealing with international business cycles have disregarded the credibility issues that play an important role in the decision to join or not a monetary union. Most of empirical applications based on asymmetric shocks have failed to account for these aspects. In this paper, we tackle this problem by relying on a regime switching approach that characterizes the position of each economy in its business cycle. Then, using desynchronisation indices based on a non parametric approach, we measure the amplitude and the duration of divergence in the business cycles in order to assess the potential stabilization cost induced by the European economic and monetary union.
urn:nbn:de:kobv:11-10046783
Keywords: 330